Genesis and development of the cultural society of wage labor - Aguiar, João Valente; Bastos, Nádia (Universidade Estadual Paulista / UNESP, 2011)
Having in mind the insertion of the production of symbolics in contemporary societies, in this article we will define some main features about the relationship between ideologic and cultural production and capitalist mode of production. In this sense, we have a double goal. On the one hand, there is the purpose to present some structural properties on the multidimensional and complex connection between the production of social life and the forms of human conscience. On the other hand, there is also the purpose to present and identify features and topics inserted in the structuration of the ideological and cultural field as a relatively autonomous space. In other words, never shadowing what connects it to the broad socioeconomic formation and, simultaneously, never disguising the specificity of the cultural field along with other spheres of social space.